STURGE-WEBER SYNDROME: A CASE REPORT - R, Janani; S, Kiruthika; Ramachandran, Arunachalam; A, Kumaresan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â To report a clinical case of Sturge-Weber syndrome (SWS) 1 year 8-month-old male child reported to Saveetha Medical College, Physiotherapy Department presented with complaints of difficulty in sitting, standing, and walking. Computed tomography brain revealed unilateral calcification and cerebral atrophy on the right side. Physical diagnosis revealed the child had left hemiparesis with developmental delay. The child had a developmental delay with a motor developmental age of 2 months. As clinical manifestations of SWS are wide, it leads to multidisciplinary approaches. Physiotherapist's knowledge is important for early diagnosis and to provide an adequate physiotherapy treatment.